New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines - Ando, Kiyoshi; Ruzzier, Enrico (Zootaxa, 2016)
In the present paper Androsus philippinus sp. nov. from Mt. Halcon (Mindoro), Euhemicera smeraldina sp. nov. from Aurora (Luzon) and Thesilea cyaneothorax sp. nov. from Nueva Viscaya (Luzon) are described, diagnosed and illustrated. Thesilea varicolor var. unicolor Kulzer 1951 is recognised as valid subspecies.